2015
DOI: 10.1371/journal.ppat.1004782
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte-Derived IFN-α/β and Epithelial IFN-λ Constitute a Compartmentalized Mucosal Defense System that Restricts Enteric Virus Infections

Abstract: Epithelial cells are a major port of entry for many viruses, but the molecular networks which protect barrier surfaces against viral infections are incompletely understood. Viral infections induce simultaneous production of type I (IFN-α/β) and type III (IFN-λ) interferons. All nucleated cells are believed to respond to IFN-α/β, whereas IFN-λ responses are largely confined to epithelial cells. We observed that intestinal epithelial cells, unlike hematopoietic cells of this organ, express only very low levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
218
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(243 citation statements)
references
References 71 publications
17
218
2
1
Order By: Relevance
“…The predominant type III IFN response and its regulation of ISG induction observed in our studies with HIEs is consistent with previous studies reporting that murine intestinal epithelial cells from poly(I:C)-injected and murine rotavirus-infected mice exhibit equal or greater fold inductions of type III IFN than type I IFN transcripts (17,55,56,58). This contrasts with results using transformed human colonic cell lines that respond to rotavirus infection and poly(I:C) with type I IFN-β at the transcript and protein levels, and type I IFN regulates ISG induction in these cells (16,42,72).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The predominant type III IFN response and its regulation of ISG induction observed in our studies with HIEs is consistent with previous studies reporting that murine intestinal epithelial cells from poly(I:C)-injected and murine rotavirus-infected mice exhibit equal or greater fold inductions of type III IFN than type I IFN transcripts (17,55,56,58). This contrasts with results using transformed human colonic cell lines that respond to rotavirus infection and poly(I:C) with type I IFN-β at the transcript and protein levels, and type I IFN regulates ISG induction in these cells (16,42,72).…”
Section: Discussionsupporting
confidence: 92%
“…However, our data demonstrate that IFNL transcripts do not parallel protein levels in epithelial cells during rotavirus infection. Hematopoietic cells can produce IFN-λ protein in response to multiple viruses (57), and a recent study has demonstrated that steady-state IFN-λ in the intestine may actually originate from CD45 + hematopoietic cells rather than epithelial cells in uninfected mice (56). Taken together, the HIE and mouse data suggest that the predominant source of the IFN-λ protein in the small intestine in response to rotavirus infection may be of hematopoietic rather than epithelial origin.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…IFN-ls form a heterodimer receptor complex that consists of the unique IL28Ra and IL10Rb (Kotenko et al, 2003;Sheppard et al, 2003). Although both type I and type III interferons induce similar interferon-stimulated genes (ISGs) through the classic JAK-STAT pathway (Marcello et al, 2006;Zhang et al, 2011;Zhou et al, 2007), IFN-l receptors are only expressed in specific organs or tissues, suggesting that IFN-ls have different immune functions in vivo (de Weerd & Nguyen, 2012;Doyle et al, 2006;Mahlakõiv et al, 2015;Mordstein et al, 2010;Sommereyns et al, 2008).…”
Section: Introductionmentioning
confidence: 99%